Notas adicionais sobre Mabea angularis Hollander (Euphorbiaceae), primeira citação para o estado do Pará, Brasil - Trindade, Maria José de Sousa (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2020)
Mabea angularis Hollander is a new record for the State of Pará. The first description of its flowers, which were unknown in the literature, is presented.